Performance of seawater-derived Mg(OH)2 as a sustainable coating solution for hydrogen sulfide-induced corrosion mitigation in concrete pipes - Janelle Patricia S. Moa; Bea Angela C. Gaw; John Louis O. Co; Kyle Anderson C. Coo; Kenneth Jae T. Elevado; Cheryl Lyne C. Roxas (Cleaner Engineering and Technology)
In the Philippines, concrete pipe systems are critical for wastewater management, flood control, and irrigation, accounting for approximately 70% of all installations. These systems often operate in anaerobic environments, making them vulnerable to corrosion from hydrogen sulfide. While commonly available methods like polyurethane and epoxy tar coal pitch are effective, modern studies have revealed that such products detrimentally affect the environment. As such, this study investigates the feasibility of a sustainable concrete surface coating using seawater-derived magnesium hydroxide (Mg(OH)2) as an alternative to commercially available options. Six distinct coating ratios were prepared with varying proportions of seawater (SW)-derived and commercially available (CA) Mg(OH)₂: 0% SW - 100% CA, 25% SW - 75% CA, 50% SW - 50% CA, 75% SW - 25% CA, and 100% SW - 0% CA, with four replicates for each mixture. The specimens were subjected to a 4M sulfuric acid solution for four days to assess compressive strength, weight loss, surface pH, and surface roughness. A life cycle assessment was also conducted for the different coating ratios, and response surface methodology (RSM) was employed to determine the optimal coating ratio. Results indicated that samples with pure Mg(OH)2 coatings exhibited the highest weight losses, while increased proportions of the commercial coating resulted in progressively lower weight losses. This trend was also reflected in the average post-exposure pH, compressive strength, and surface roughness, with the best performance observed in coatings composed of pure commercially available Mg(OH)₂. Although the 100% SW - 0% CA specimens did not meet the required pH and compressive strength standards, other coating ratios could satisfy the acceptance criteria. Notably, a significant difference of 3,092,680 mPt was observed between pure commercially available and seawater-derived Mg(OH)₂ coatings when scaled on a flood control project case study. Based on the results, RSM analysis suggested an optimal coating ratio of 40% SW - 60% CA Mg(OH)2. This study highlights the potential of seawater-derived Mg(OH)2 as a sustainable alternative for mitigating hydrogen sulfide-induced corrosion in concrete pipe systems.